Eksplorasi Etnomatematika pada Kue Tradisional di Daerah Magelang - Idha Isnaningrum; Muhammad Abdul Wahab (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The purpose of this study was to identify ethnomathematics concepts and describe the ethnomathematics relationships in traditional cakes typical of the Magelang region. The research method used was ethnography using a qualitative approach. The techniques used in collecting this data used observation techniques, interview techniques and documentation techniques. In analyzing the data in this study using triangulation. The object of this research is a traditional cake typical of the Magelang area with three research subjects or informants. The results of data analysis concluded that there are several comparative concepts, flat shape patterns and geometric patterns in Magelang traditional cakes. The concept of a flat shape found in traditional Magelang cakes is a circle and a rectangle. While the concept of building space is a ball, beam and cylinder